2022
DOI: 10.1021/acsaem.2c03095
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Solvent Additives Enabling High-Efficiency Organic Solar Cells without Thermal Annealing

Abstract: Additive strategy is considered to be an effective way to achieve high-efficiency organic solar cells (OSCs). However, for heat-sensitive material systems, such as D18 and its derivatives, solvent additives with high-boiling points that need to be fully removed by high-temperature annealing often fail to optimize the device performance. Herein, based on the D18-Cl:Y6-based device, we chose the volatile solvent tetrahydrofuran (THF) as the solvent additive, which can achieve effects similar to high-boiling-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several volatile solvent additives were reported in nonfullerene-based systems recently. 85,86 Tao et al utilized tetrahydrofuran (THF, 66 °C, Fig. 1b) as the additive in D18-Cl:Y6 (Fig.…”
Section: Solvent Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several volatile solvent additives were reported in nonfullerene-based systems recently. 85,86 Tao et al utilized tetrahydrofuran (THF, 66 °C, Fig. 1b) as the additive in D18-Cl:Y6 (Fig.…”
Section: Solvent Additivesmentioning
confidence: 99%
“…2) based OSCs and obtained a higher PCE of 17.70% than the control device without THF (16.85%) (Table 2). 85 According to the TEM and AFM results, THF can improve the morphology of the active layer with enhanced phase separation and a smoother surface, leading to more efficient charge carrier transport and charge collection. Using the space charge limited current (SCLC) method, they confirmed that higher and more balanced charge carrier mobilities were achieved in the device with THF, thus increasing the J SC from 26.20 mA cm −2 to 27.02 mA cm −2 .…”
Section: Solvent Additivesmentioning
confidence: 99%
“…These additives have a higher boiling point as compared to the main solvent, leading to a slower evaporation rate during the film preparation, thus allowing for fine-tuning of the film crystallinity, as well as the phase separation in the case of blends. 15,22–25…”
Section: Introductionmentioning
confidence: 99%
“…These additives have a higher boiling point as compared to the main solvent, leading to a slower evaporation rate during the film preparation, thus allowing for fine-tuning of the film crystallinity, as well as the phase separation in the case of blends. 15,[22][23][24][25] The second category, solid additives, operates distinctively from their solvent counterparts, first because they alter the intermolecular interaction among p-conjugated compounds, and second because they are incorporated into the films, so in principle they do not require high temperature for their removal. [26][27][28] Such a scenario is particularly interesting as it avoids the risk of film degradation which inevitably leads to a reduction in device performance.…”
Section: Introductionmentioning
confidence: 99%